2020
DOI: 10.1111/jog.14349
|View full text |Cite
|
Sign up to set email alerts
|

Can neutrophil‐to‐lymphocyte and monocyte‐to‐lymphocyte ratios be useful markers for predicting missed abortion in the first trimester of pregnancy?

Abstract: Aim To explore whether neutrophil‐to‐lymphocyte ratio (NLR) and monocyte‐to‐lymphocyte ratio (MLR) could predict missed abortion (MA) at 7–13 week's gestation. Methods A total of 363 women with a diagnosis of MA and 232 women with normal pregnancy at 7–13 week's gestation, who visited our hospital from June 2012 to May 2018 were retrospectively analyzed. At 7 week's gestation, total and differential leukocyte counts, NLR and MLR were compared between women with MA (n = 69) and normal controls (n = 53). The rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 55 publications
0
3
2
Order By: Relevance
“…Wang et al analyzed MA cases at week 7 in terms of WBC value. 16 Contrary to our data, they reported that the risk of MA increased when this value was below 8x10 3 /μL in MA cases (84% sensitivity and 54% specificity). Wang et al further explored the effects of progesterone on the total or differential WBC value, NLR and MLR in MA cases.…”
Section: Sensitivitycontrasting
confidence: 99%
See 4 more Smart Citations
“…Wang et al analyzed MA cases at week 7 in terms of WBC value. 16 Contrary to our data, they reported that the risk of MA increased when this value was below 8x10 3 /μL in MA cases (84% sensitivity and 54% specificity). Wang et al further explored the effects of progesterone on the total or differential WBC value, NLR and MLR in MA cases.…”
Section: Sensitivitycontrasting
confidence: 99%
“…2,7,29 The NLR threshold value calculated to predict MA was reported to be below 2.4 in Wang et al's study and below 5.72 in Kim's study. 16,29 The cut-off value in these studies is in the opposite direction with our results. The difference between these studies in the literature is due to 2 reasons.…”
Section: Sensitivitycontrasting
confidence: 99%
See 3 more Smart Citations